2020
DOI: 10.1136/ijgc-2020-001825
|View full text |Cite
|
Sign up to set email alerts
|

Central radiology assessment of the randomized phase III open-label OVHIPEC-1 trial in ovarian cancer

Abstract: IntroductionHyperthermic intraperitoneal chemotherapy (HIPEC) improved investigator-assessed recurrence-free survival and overall survival in patients with stage III ovarian cancer in the phase III OVHIPEC-1 trial. We analyzed whether an open-label design affected the results of the trial by central blinded assessment of recurrence-free survival, and tested whether HIPEC specifically targets the peritoneal surface by analyzing the site of disease recurrence.MethodsOVHIPEC-1 was an open-label, multicenter, phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…As described previously, HIPEC may alter the recurrence pattern in ovarian cancer and was associated with a lower rate of peritoneal recurrence, which was consistent with our findings . Ceresoli et al reported that recurrence in the peritoneum was associated with poor OS among patients who underwent ICS with HIPEC.…”
Section: Discussionsupporting
confidence: 92%
“…As described previously, HIPEC may alter the recurrence pattern in ovarian cancer and was associated with a lower rate of peritoneal recurrence, which was consistent with our findings . Ceresoli et al reported that recurrence in the peritoneum was associated with poor OS among patients who underwent ICS with HIPEC.…”
Section: Discussionsupporting
confidence: 92%
“… 27 Five studies were excluded due to not being randomized 28 , 29 and due to researching outcomes unrelated to our analysis. 30 , 31 , 32 The eligible studies were conducted in South Korea, 22 Spain, 23 USA, 24 , 27 the Netherlands, 25 Greece 26 and three of them were multicenter. 22 , 24 , 25 Overall 737 patients were randomized across six trials; among these four studies (519 patients) 22 , 23 , 25 , 27 concerned the experimental use of HIPEC in primary ovarian cancer and two (218 patients) its investigational use in recurrent settings.…”
Section: Resultsmentioning
confidence: 99%
“…These latter 2 observations indicate that any potential surgical bias has had minimal prognostic impact. Furthermore, central revision of recurrence-free survival ruled out radiological bias . Regarding the alleged imbalance in specific baseline characteristics such as histologic subtype, the general principle of randomization ensured equality of prognosis based on all known and unknown prognostic factors.…”
Section: Epithelial Ovarian Cancermentioning
confidence: 99%